Defunctioning Ileostomy After Low Anterior Resection of Rectum: Morbidity Related to Fashioning and Closure - Nikolaos Gouvas; Dimitrios Manatakis; Christos Agalianos; Nikoletta Dimitriou; Ioannis Baloyiannis; George Tzovaras; Evangelos Xynos (Medicina)
Background and Objectives: The aim of this study was to assess any predisposing factors to the morbidity of fashioning and reversal of diverting ileostomy in a prospective cohort of patients who have undergone TME and low colo-rectal or colo-anal anastomosis for rectal cancer. Materials and Methods: Consecutive patients with rectal cancer undergoing low anterior resection and a defunctioning loop ileostomy in three surgical units from 2016 to 2020 were included in the study and retrospectively analyzed. Results: One hundred eighty-two patients from three centres were included. Ileostomy-related mortality was 0.5%, attributed to renal failure.. Ileostomy-related morbidity was 46%. Postoperative ileus was seen in 37.4%, and dehydration in 18.8% of the patients. The readmission rate for ileostomy-related reasons was 15.4%. Stoma care was problematic in 15.7% or poor in 7% of the cases. Advanced age, male gender and obesity were independent risk factors for ileostomy-related morbidity. Ileostomy was reversed in 165 patients. The morbidity in 165 patients was 16%. Ileus was seen in 10.3%, anastomotic leak in 4.8% and wound infection in 12.7% of the cases. One patient died because of an anastomotic leak. No predisposing factors that affect the outcomes of ileostomy closure were identified. Conclusions: Diverting ileostomy-related morbidity is high. Life threatening dehydration and renal failure from ileus is more commonly seen in elderly, male and obese patients and should be anticipated. Ileostomy closure-related morbidity is low.